2020
DOI: 10.7759/cureus.6880
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on the Participation of Neurosurgery Resident Physicians in Their Care

Abstract: Introduction Surgical residents play vital roles in day-today patient care as well as in the operating room. However, there is a paucity of literature regarding patients' perspectives on neurosurgical residents and their participation in their care. This current study investigates the knowledge, attitudes, and beliefs of patients regarding neurosurgical residents and their involvement in their healthcare process. Methods Patients older than 18 years who had undergone brain or spine surgery were requested to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Notably, international studies of private settings have found that paying patients are firmly in favour of trainee involvement in surgery, and feel that surgical training should take place in the private sector worldwide. [23][24][25][26] Across these studies, up to 90-97% of respondents thought that training should occur in private hospitals and up to 85.7-88% of private patients were willing to allow a supervised trainee to perform part of their operation. These findings are highly relevant, as patients often seek care in the private sector hoping to access the expertise of a specific specialist or medical team, and there may be the assumption that said specialist will perform all requisite surgical procedures in their entirety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, international studies of private settings have found that paying patients are firmly in favour of trainee involvement in surgery, and feel that surgical training should take place in the private sector worldwide. [23][24][25][26] Across these studies, up to 90-97% of respondents thought that training should occur in private hospitals and up to 85.7-88% of private patients were willing to allow a supervised trainee to perform part of their operation. These findings are highly relevant, as patients often seek care in the private sector hoping to access the expertise of a specific specialist or medical team, and there may be the assumption that said specialist will perform all requisite surgical procedures in their entirety.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are highly relevant, as patients often seek care in the private sector hoping to access the expertise of a specific specialist or medical team, and there may be the assumption that said specialist will perform all requisite surgical procedures in their entirety. [23][24][25][26]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation